The transdiagnostic role of event-related rumination on internalizing and externalizing symptoms during the pandemic: a two-wave longitudinal study - Kim, Bin-Na; Kang, Hyo Shin; Park, Jungkyu (Frontiers in Psychology, 2025)
BackgroundRumination is a well-established transdiagnostic vulnerability. However, few studies have explored the transdiagnostic role of event-related rumination. Moreover, there is a paucity of longitudinal studies clarifying the temporal precedence of event-related rumination. Therefore, this study aimed to longitudinally examine the mediating paths of event-related rumination between perceived stress and diverse symptomatic dimensions.MethodsA representative sample of Korean adults (N = 316) was recruited online and they completed a package of self-reported measures twice over a one-year period. Using prospective two-wave data collected during the pandemic, longitudinal indirect effects were examined using the hypothesized path model.ResultsAs expected, intrusive rumination acted as a transdiagnostic mediator in both internalizing and externalizing psychopathology and was positively associated with all subsequent symptom dimensions, except mania. Meanwhile, the beneficial role of deliberate rumination was less-transdiagnostic.ConclusionThese initial findings suggest that event-related rumination could be considered a transdiagnostic mediator and a target for prevention and intervention to maintain mental health during and after the pandemic.